Orbital Atherectomy Plaque Modification Assessment of the Femoropopliteal Artery Via Intravascular Ultrasound (TRUTH Study). (October 2015) - Babaev, Anvar; Zavlunova, Susanna; Attubato, Michael J.; Martinsen, Brad J.; Mintz, Gary S.; Maehara, Akiko
Objective: The Tissue Removal Assessment with Ultrasound of the SFA and Popliteal (TRUTH) study assessed the performance of the orbital atherectomy system (OAS) to treat femoropopliteal arteries, including determining its effect on plaque removal. Methods: Patients with symptomatic femoropopliteal peripheral arterial disease were treated with the OAS followed by adjunctive balloon angioplasty (BA). Intravascular ultrasound (IVUS) images were collected pre- and post-OAS and post-OAS BA. Patients were followed through 12 months post-procedure. Results: Twenty-nine lesions were treated with OAS-BA in 25 patients. The mean maximum balloon inflation pressure was 5.2 ± 1.2 atm. Virtual histology IVUS (VH-IVUS) analysis revealed at the maximum calcium ablation site that calcium reduction was responsible for 86% of the lumen area increase. The minimum lumen area increased from 4.0 mm 2 to 9.1 mm 2 (<.0001), and the percentage of area stenosis decreased from 76.9% to 43.0% (<.0001) after OAS-BA. At 12 months, the target lesion revascularization rate was 8.2%, and ankle–brachial index and Rutherford classification improved significantly from baseline through follow-up. Conclusion: The VH-IVUS analysis reveals that OAS modifies the calcified component of the plaque burden. It is hypothesized that calcium modification by OAS changes the lesion compliance, allowing for low pressure adjunctive BA. The clinical outcomes were favorable through 12-month follow-up.